Direct and indirect effects of tree canopy facilitation in the recruitment of Mediterranean oaks - Caldeira, Maria C.; Ibáñez, Inés; Nogueira, Carla; Bugalho, Miguel N.; Lecomte, Xavier; Moreira, Andreia; Pereira, João S. (Journal of Applied Ecology, 2014)
* Tree recruitment in Mediterranean ecosystems is strongly limited at the seedling stage by drought. Increasing evidence shows the critical positive role of the canopy nurse effect on seedling survival which results from direct and indirect, positive and negative interactions between species. * Most studies, however, have only focused on the effects of tree canopy on water and light, ignoring other critical factors affecting seedling regeneration, such as canopy effects on high temperatures and the competing herb biomass. * Here, we evaluate how tree canopy cover and removal of herbs affect the survival and growth of seedlings of two dominant Mediterranean Quercus species during a 3-year study. We use an integrated model that combines several data sets to quantify and predict regeneration dynamics along environmental gradients of soil moisture, temperature and light. * Low soil moisture, increased soil temperature and herb biomass negatively affected seedling survival of both Quercus species. Seedling growth was positively associated with increasing soil moisture and light. * Although tree canopy cover directly facilitated seedling survival in both Quercus species, it also negatively affected herb biomass and thus indirectly facilitated the survival of Quercus suber, but not of Quercus ilex seedlings at low levels of soil moisture. * Overall, tree canopies increased seedling survival but not growth during the establishment phase, mainly by ameliorating the effects of low soil moisture and high temperatures. Tree canopy indirectly facilitated survival of Q. suber seedlings by negatively affecting the competing herb layer. * Synthesis and applications. To improve tree recruitment and conserve Mediterranean Quercus woodlands, the removal of herbs should be integrated into management plans for dry habitats. Interactions between abiotic and biotic factors may also effect the regeneration of these tree species. In particular, a healthy tree canopy will become important for providing conditions to facilitate seedling establishment if these habitats become drier and warmer, as predicted by some climate change scenarios.
Keywords: climate change; herb management; high temperatures; positive interactions; Quercus ilex; Quercus suber; tree recruitment

Effects of forest certification on the ecological condition of Mediterranean streams - Dias, Filipe S.; Bugalho, Miguel N.; Rodríguez-González, Patricia M.; Albuquerque, António; Cerdeira, J. Orestes (Journal of Applied Ecology, 2014)
1. Forest certification, a proxy for sustainable forest management, covers more than 10% of the world’s forests. Under forest certification, forest managers and landowners must comply with environmental, economic and social management standards aiming to promote forest conservation. Despite an increasing area of certified forests, there is a dearth of data on how forest certification is affecting the conservation of forest ecosystems and associated habitats. 2. Here, we assess the effects of Forest Stewardship Council (FSC) certification, one of the largest certification schemes in the world, on the ecological condition of streams crossing Mediterranean evergreen oak woodlands. 3. We used the Stream Visual Assessment Protocol (SVAP) to compare the ecological condi- tion of streams located in areas with 3 and 5 years of certification, in non-certified areas and in least disturbed streams. 4. Forest certification positively affected the ecological condition of the surveyed streams, but its effects were only measurable after 5 years of certification. Streams with 5 years of certification had more continuous, dense and diverse riparian vegetation when compared to streams located in non-certified areas. Moreover, the condition of streams located in areas with 5 years of forest certification was similar to the condition of least disturbed streams. 5. Synthesis and applications. Forest certification promotes the ecological condition of streams occurring within Mediterranean evergreen oak woodlands. This mainly happens because in areas under forest certification, managers and landowners have to comply with management practices that require them to remove or reduce the main causes for stream deg- radation, allowing riparian habitats to recover. Within landscapes with large and increasing areas under forest certification, such as the Mediterranean cork oak woodlands, the positive effects of certification on the ecological condition of streams may spread across the hydro- graphic network in the medium to long term.
Keywords: Cork oak; Forest management; Forest Stewardship Council; freshwater habitats; rapid bio-assessment protocol; Riparian vegetation; Stream Visual Assessment Protocol

Assessing foraging strategies of herbivores in Mediterranean oak woodlands: a review of key issues and selected methodologies - Ferraz de Oliveira, Maria Isabel; Lamy, Elsa; Bugalho, Miguel N.; Vaz, Margarida; Pinheiro, Cristina; Cancela d’Abreu, Manuel; Capela e Silva, Fernando; Sales-Baptista, Elvira; Isabel, Maria; Oliveira, Ferraz De; Capela, Fernando (Agroforestry Systems, 2013)
Montados are agro-silvo-pastoral ecosys- tems, typical of the Southwest Iberian Peninsula, of high socio-economic and conservation importance, where grazing is a dominant activity. Montados are characterized by an open tree canopy of Quercus sp. and a diverse undercover of shrubs and grasslands that constitute the plant food resources for grazing animals. Plant food resources of Montados are highly variable, both spatially and seasonally, in quantity and quality. Reliable and easy to use methods to monitor grazing are necessary to allow proper understanding of foraging strategies of grazing animals and to set sustainable grazing management. We describe the main characteristics of the plant food resources available for grazing animals, striking its variability, and revise the potential of using N-alkanes and saliva proteome methods to assess foraging strategies in Montados. In a scenario of dynamic multiple choices, we discuss the use of n-alkane methodology for the simultaneous estimation of diet composition and voluntary intake and saliva proteome as a mean of increasing the knowledge on diet adjustments.
From Duplicate 2 (From Duplicate 2 (
Keywords: Agro-silvo- pastoral systems; foraging behavior; Grazing ecology; montado/dehesa; N-alkanes; Salivary proteins

Is forest certification targeting areas of high biodiversity in cork oak savannas? - Dias, Filipe S.; Bugalho, Miguel N.; Orestes Cerdeira, J.; João Martins, M. (Biodiversity and Conservation, 2012)
Over the last four decades the world has been losing biodiversity at an alarming rate despite the increasing number of protected areas (PAs). Certiﬁed forest management may complement the role of PAs in protecting biodiversity. Forest certiﬁcation aims to promote sustainable forest management and to maintain or enhance the conservation value of certiﬁed forests. The area of forest under certiﬁed forest management has grown quickly over the past decade. Forest Stewardship Council (FSC) certiﬁcation, for example, currently covers 148 million hectares, i.e., 3.7 % of the world’s forests. In spite of such increase there is, however, a dearth of information on how forest certiﬁcation is related to biodiversity. In this study we assessed if FSC certiﬁcation is being applied in high biodiversity areas in cork oak savannas in Portugal by comparing biodiversity values of certiﬁed and non-certiﬁed areas for birds, reptiles and amphibians. We calculated the relative species richness and irreplaceability value for each group of species in certiﬁed and non-certiﬁed areas and compared them using randomization tests. The biodiversity value of certiﬁed areas was not signiﬁcantly greater than that of non-certiﬁed areas. Since FSC certiﬁcation is expanding quickly in cork oak savannas it is important to consider the biodiversity value of these areas during this process. Prioritizing areas of high biodiversity value would enhance the conservation value of forest certiﬁcation and facilitate integrating certiﬁcation with other conservation initiatives.
Keywords: Biodiversity conservation; Conservation strategies; Forest management; Irreplaceability; Mediterranean; Species richness

Mediterranean cork oak savannas require human use to sustain biodiversity and ecosystem services - Bugalho, Miguel N.; Caldeira, Maria C.; Pereira, João S.; Aronson, James; Pausas, Juli G. (Frontiers in Ecology and the Environment, 2011)
Mediterranean cork oak savannas, which are found only in southwestern Europe and northwestern Africa, are ecosystems of high socioeconomic and conservation value. Characterized by sparse tree cover and a diversity of understory vegetation – ranging from shrub formations to grasslands – that support high levels of biodiversity, these ecosystems require active management and use by humans to ensure their continued existence. The most important product of these savannas is cork, a non-timber forest product that is periodically harvested without requiring tree felling. Market devaluation of, and lower demand for, cork are causing a decline in management, or even abandonment, of southwestern Europe’s cork oak savannas. Subsequent shrub encroachment into the savanna’s grassland components reduces biodiversity and degrades the services provided by these ecosystems. In contrast, poverty-driven overuse is degrading cork oak savannas in northwestern Africa. “Payment for ecosystem services” schemes, such as Forest Stewardship Council (FSC) certification or Reducing Emissions from Deforestation and Degradation and enhancement of carbon stocks (REDD+) programs, could produce novel economic incentives to promote sustainable use and conservation of Mediterranean cork oak savanna ecosystems in both Europe and Africa.
Keywords: Biodiversity conservation; Carbon storage; Cork oak savannas; ecosystem services; Management practices; Quercus suber; Shrub encroachment (voyant)

The composition of the diet of red deer (Cervus elaphus) in a Mediterranean environment: a case of summer nutritional constraint? - Bugalho, Miguel N.; Milne, John a (Forest Ecology and Management, 2003)
The composition of the diet of red deer (Cervus elaphus) in a Mediterranean environment, in southern Portugal, was estimated during summer 1995–1997 using n-alkane analysis. Standing crop of herbage layer biomass was estimated between June and September 1995–1997 using the clipping quadrat method. There was a large variability between years in the availability of the herbage layer biomass. Biomass was three fold greater and availability of legumes higher in a wet than in a dry year. Live green material was available in the herbage layer in June, but not thereafter, even during a wet year. Red deer ingested a higher proportion of browse in summer during drier years (0.83–0.89) than during a wet year (0.47). In the drier years, the herbage layer was replaced in the diet by browse species that were uneaten in the wet year. Contrary to Atlantic environments, where red deer include a large proportion of browse in their diets during winter, summer is likely to be a season of nutritional constraint for red deer inhabiting Mediterranean environments
Keywords: browse; cervus elaphus; diet composition; Mediterranean